2022
DOI: 10.1002/ptr.7566
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flaxseed oil consumtion on blood pressure among patients with metabolic syndrome and related disorders: A systematic review and meta‐analysis of randomized clinical trials

Abstract: We systematically reviewed randomized clinical trials (RCTs) to elucidate the overall effects of flaxseed oil consumption on blood pressure (BP) in patients with metabolic syndrome and related disorders. PubMed, Scopus, Cochrane Library, and ISI Web of Science databases were systematically searched until March 31, 2020, to find RCTs that examined the effect of flaxseed oil consumption on BP. Weighed mean difference (WMD) was pooled using a random‐effects model. Standard methods were used for the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Numerous systematic reviews and meta-analyses investigated the health benefits of consuming flaxseed oil. A recent systematic review of randomized clinical trials in patients with metabolic syndrome and related disorders reported that flaxseed oil consumption significantly reduced systolic blood pressure, but not diastolic blood pressure [22]. Additionally, Musazadeh et al [23] conducted a meta-analysis that aimed to determine the impact of flaxseed oil on biomarkers of oxidative stress, and found a significant decrease in malondialdehyde levels and an increase in total antioxidant capacity levels, indicating that it may be useful in reducing oxidative stress and strengthening the antioxidant defense system in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous systematic reviews and meta-analyses investigated the health benefits of consuming flaxseed oil. A recent systematic review of randomized clinical trials in patients with metabolic syndrome and related disorders reported that flaxseed oil consumption significantly reduced systolic blood pressure, but not diastolic blood pressure [22]. Additionally, Musazadeh et al [23] conducted a meta-analysis that aimed to determine the impact of flaxseed oil on biomarkers of oxidative stress, and found a significant decrease in malondialdehyde levels and an increase in total antioxidant capacity levels, indicating that it may be useful in reducing oxidative stress and strengthening the antioxidant defense system in humans.…”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous randomized controlled trials (RCTs) and a rencent review have shown that flaxseed and its constituent parts can lower BP. [13][14][15][16][17] Despite growing body of evidence, there is inconsistency amongst trials examining the effects of flaxseed on BP. Two meta-analyses published in 2015 evaluated the anti-hypertensive benefits of flaxseed and flaxseed-derived products on BP.…”
Section: Introductionmentioning
confidence: 99%
“…Natural lipids such DOI: 10.1002/mnfr.202300535 as fish oil and flaxseed oil are highquality sources of essential fatty acids, and their positive effects on Alzheimer's disease, diabetes, and hypertension are documented. [1][2][3] However, the limited natural lipid resources are difficult to meet the growing human health needs. Artificially designed lipids (structural lipids) become an effective strategy to address this dilemma.…”
Section: Introductionmentioning
confidence: 99%